Avaliação da atividade antibacteriana e prospecção fitoquímica de Solanum paniculatum Lam. e Operculina hamiltonii (G. Don) D. F. Austin & Staples, do semi-árido paraibano Evaluation of antibacterial activity and phytochemical prospection of Solanum paniculatum Lam. and Operculina hamiltonii (G. Don) D. F. Austin & Staples from the semi-arid region of Paraíba State, Brazil - K.M.S Lôbo; A.C.R Athayde; A.M.A Silva; F.F.G Rodrigues; I.S Lôbo; D.A.C Bezerra; J.G.M Costa (Universidade Estadual Paulista, 2010)
Devido ao aparecimento de populações de parasitos resistentes, as drogas farmacêuticas, alternativas de controle, estão sendo pesquisadas utilizando plantas medicinais. O objetivo deste estudo foi avaliar a atividade antibacteriana e realizar a análise fitoquímica do extrato etanólico de duas espécies do semi-árido paraibano, Solanum paniculatum Lam. e Operculina hamiltonii (G. Don) D. F. Austin & Staples. As referidas espécies são muito utilizadas pela população rural contra verminoses gastrintestinais de ovinos. A prospecção fitoquímica foi obtida a partir dos extratos etanólicos para análise dos constituintes químicos existentes nas duas espécies. As análises dos extratos indicaram a presença de taninos flobabênicos, flavononóis, flavononas e alcalóides em ambas as espécies. A atividade antibacteriana foi determinada inicialmente pelo método de difusão em cavidade. A espécie S. paniculatum apresentou atividade contra Staphylococcus aureus (ATCC 12692), Escherichia coli (ATCC 25922) e Pseudomonas aeruginosa (ATCC 15442), no entanto O. hamintonii não demonstrou atividade contra as linhagens bacterianas testadas. The emergence of resistant parasite populations has led to the study of pharmaceutical drugs, which represent an alternative control. This study aimed to evaluate the antibacterial activity and to perform the phytochemical analysis of the ethanol extract from two species belonging to the semi-arid region of Paraíba State, Brazil: Solanum paniculatum Lam. and Operculina hamiltonii (G. Don) D. F. Austin & Staples. Such species have been largely used by the rural population against ovine gastrointestinal helminthes. Phytochemical prospection was obtained from ethanol extracts for analysis of chemical compounds present in both species. Extract analyses indicated the presence of condensed tannins, flavonols, flavanones, and alkaloids in both species. The antibacterial activity was initially determined by the cavity method. The species S. paniculatum had activity against Staphylococcus aureus (ATCC 12692), Escherichia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 15442); however, O. hamintonii did not present activity against the tested bacterial strains.